2010
DOI: 10.1074/jbc.m110.126318
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human VPS4A by ESCRT-III Proteins Reveals Ability of Substrates to Relieve Enzyme Autoinhibition

Abstract: VPS4 proteins are AAA؉ ATPases required to form multivesicular bodies, release viral particles, and complete cytokinesis. They act by disassembling ESCRT-III heteropolymers during or after their proposed function in membrane scission. Here we show that purified human VPS4A is essentially inactive but can be stimulated to hydrolyze ATP by ESCRT-III proteins in a reaction that requires both their previously defined MIT interacting motifs and ϳ50 amino acids of the adjacent sequence. Importantly, C-terminal fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
64
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 72 publications
(109 reference statements)
10
64
3
Order By: Relevance
“…To better understand the contributions of the linker region, biochemical characterization was undertaken. The analysis of recombinant Vps4 mutant proteins demonstrated that loss of the linker region caused an increase in maximal ATPase activity, a result that is consistent with the idea that the linker is involved in an auto-inhibition mechanism (21). However, the protein concentration necessary to induce oligomerization was higher for linker-deleted Vps4 than for the wild-type protein.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…To better understand the contributions of the linker region, biochemical characterization was undertaken. The analysis of recombinant Vps4 mutant proteins demonstrated that loss of the linker region caused an increase in maximal ATPase activity, a result that is consistent with the idea that the linker is involved in an auto-inhibition mechanism (21). However, the protein concentration necessary to induce oligomerization was higher for linker-deleted Vps4 than for the wild-type protein.…”
Section: Discussionsupporting
confidence: 55%
“…However, deleting both the MIT domain and the linker abolished Vps4 hydrolysis activity at the concentrations examined (Vps4(⌬1-116), Fig. 3B), which is in contrast to human VPS4A, where deletion of the corresponding residues (1-100) results in higher ATPase activity when compared with the wildtype protein (21). Our data suggested that the MIT domain and the linker affect both oligomerization and ATPase activity of the assembled Vps4 complex.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 42%
See 2 more Smart Citations
“…VPS4 enzymes are recruited to their sites of action, at least in part, by binding to a variety of different and often partially redundant MIM elements that are exposed upon ESCRT-III filament formation (19,(32)(33)(34)(35)(36)(37)(38). In addition to these general ESCRT-III interactions, two binary complexes, CHMP1-IST1 and LIP5-CHMP5, play particularly important roles in VPS4 recruitment and activation.…”
mentioning
confidence: 99%